2008
DOI: 10.4049/jimmunol.180.12.8073
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Expression on T Cell Is a Self-Control Negative Regulator of Type 1 Immune Response

Abstract: The cytokine milieu and dendritic cells (DCs) direct Th1 development. Yet, the control of Th1 polarization by T cell surface molecules remains ill-defined. We here report that CD47 expression on T cells serves as a self-control mechanism to negatively regulate type 1 cellular and humoral immune responses in vivo. Th2-prone BALB/c mice that lack CD47 (CD47−/−) displayed a Th1-biased Ab profile at steady state and after immunization with soluble Ag. CD47−/− mice mounted a T cell-mediated exacerbated and sustaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 62 publications
8
40
1
Order By: Relevance
“…Consistent with this active immunization and protection, naive CD47KO mice were found to induce higher levels of virus-specific IgG antibodies and to be more effectively protected after viral infection compared to WT mice. Thus, these results suggest that CD47 negatively modulates protective immune responses, which is consistent with previous findings (22).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with this active immunization and protection, naive CD47KO mice were found to induce higher levels of virus-specific IgG antibodies and to be more effectively protected after viral infection compared to WT mice. Thus, these results suggest that CD47 negatively modulates protective immune responses, which is consistent with previous findings (22).…”
Section: Discussionsupporting
confidence: 82%
“…It has been shown that DCs and the cytokine milieu influence a Th1 immune response. Consistent with the Th1 type IgG isotype responses in this study, a previous study demonstrated that CD47 deficiency enhanced a Th1 dominant cell response, producing IFN-␥ and a Th1-biased antibody response (22), implying that CD47 is a negative regulator of the Th1 immune response. Thus, we expected that vaccination with VLPs might promote an enhanced Th1 dominant response and in turn induce a high ratio of IgG2c isotype antibody, although similar numbers of antigen-specific CD4 ϩ and CD8 ϩ T cells were observed in the lungs of nonimmune WT and CD47KO mice, as well as in immune WT and CD47KO mice.…”
Section: Discussionsupporting
confidence: 71%
“…2F), indicating that survivors of the contraction phase have converted to CD47 high cells. Notably, CD47 2/2 Tg T cells transferred into CD47 2/2 mice displayed an effector, rather than T CM phenotype, at this later time point, supporting the concept that enhanced cell survival, T-bet expression, and Th1 responses as seen in CD47-deficient mice (13,21) correlate with impaired CD4 T CM differentiation.…”
Section: Cd47 High Status Marks Early T CM Precursors In Primary Respmentioning
confidence: 50%
“…Also, equal proportions of the two memory CD4 T cell subsets are generated after Listeria monocytogenes infection in WT mice: the T-bet high cells that lack CCR7 and rapidly produce IFN-g, and thus resemble Th1 effector memory cells; and the T-bet low cells that express CCR7 and produce none of the lineage-defining cytokines, and therefore resemble T CM (25,31). Lack of CD47 expression enhances T-bet expression on CD4 T cells as well as exacerbates and sustains T cell-mediated contact hypersensitivity response, which correlates with an enhanced type 1 IR (13,32). Therefore, the lower frequency of T CM seen in CD47 2/2 hosts in the absence of lymphosplenomegaly may be best explained by increased T-bet combined with decreased production of IL-7 in CD47 2/2 when compared with WT hosts (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation